The posthumous Nobel Prize in chemistry - Strom, E. Thomas; Mainz, Vera V.; American Chemical Society. Division of the History of Chemistry (Washington, DC American Chemical Society, 2017)
A humorous overview and history of the Nobel Prizes, generally, and the chemistry prize in particular; who won, and why.
volume 1. Correcting the errors and oversights of the Nobel Prize Committee -- volume 2. Ladies in waiting for the Nobel Prize
Electronic reproduction.
Keywords: Chemistry -- Awards -- History; Nobel Prizes -- History; Nobel Prize winners; Women Nobel Prize winners; Electronic books